2021
DOI: 10.1093/femsec/fiab039
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome variation during culture growth of the European house dust mite,Dermatophagoides pteronyssinus

Abstract: In culture, the house dust mite, Dermatophagoides pteronyssinus, shows different growth patterns, but the composition and changes in the associated microbial community during mite culture growth are poorly known. In this study, we analyzed temporal changes in microbial communities including ‘internal’ communities (inside mites, ingested) and ‘environmental’ communities (from culture environment). Microbial community structure was correlated with guanine content (a nitrogenous waste product of mites) and mite p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 84 publications
3
17
0
Order By: Relevance
“…It is also possible that the positive presence of Bartonella -like bacteria cannot overcome the suppressive effects of the fecal-associated microorganisms that are correlated with decreased mite fitness. We have previously shown that some of the fecal treatment-associated microorganisms (i.e., Staphylococcus , Candida , and Aspergillus ) are correlated to the mite waste deposit guanine ( Nesvorna et al, 2021 ), and we hypothesize that these microbes decrease mite fitness either through the production of toxic metabolic wastes or through direct competition with the mites to nutrients, or both. In laboratory experiments, mite population growth has shown density-dependent patterns ( Pekar and Hubert, 2008 ; Rybanska et al, 2016 ), which lead to decreased growth rates at higher densities.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…It is also possible that the positive presence of Bartonella -like bacteria cannot overcome the suppressive effects of the fecal-associated microorganisms that are correlated with decreased mite fitness. We have previously shown that some of the fecal treatment-associated microorganisms (i.e., Staphylococcus , Candida , and Aspergillus ) are correlated to the mite waste deposit guanine ( Nesvorna et al, 2021 ), and we hypothesize that these microbes decrease mite fitness either through the production of toxic metabolic wastes or through direct competition with the mites to nutrients, or both. In laboratory experiments, mite population growth has shown density-dependent patterns ( Pekar and Hubert, 2008 ; Rybanska et al, 2016 ), which lead to decreased growth rates at higher densities.…”
Section: Discussionmentioning
confidence: 96%
“…For the fungal communities, the genera Yamadazyma and Candida were associated with the fecal treatments. Although Saccharomyces cerevisise was a compound of mite diet, the other yeasts ( Candida , Hyphopichia , and Malassezia ) have been previously identified in mite cultures and have been associated with house dust mite culture development and were associatiated with mite feces ( Klimov et al, 2019 ; Molva et al, 2019 ; Nesvorna et al, 2021 ). Yamadazyma and have been elsewhere isolated from insects, also ( Suh et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The wide range of allergens produced cause allergic rhinoconjunctivitis and asthma and contribute to other allergic skin diseases in genetically predisposed individuals. Therefore, mite allergen extracts are essential for allergy diagnosis and treatment of mite allergy [5].…”
Section: Introductionmentioning
confidence: 99%